الابداع وأهميته في العملية التعليمية - يوسف حمزة, عناية (Journal of College of Education, 2020)
The importance of creativity in the educational process stems from its duties and responsibilities that include planning, organizing, coordinating, directing and following up to achieve the desired goals and extends to work on developing performance to keep pace with the developments and developments of the age until its outputs come at the level of desired aspirations.Certainly, in light of the local and global changes, we are in dire need of developing minds characterized by scientific thinking and the ability to be creative, which is the essence of scientific and technological progress.Therefore, the present research aims to provide a theoretical framework for creativity and its importance in the educational process.The researcher reached several conclusions, including:The teacher has a major role in facilitating the creative growth of learners.Among the recommendations recommended by the researcher are:- The necessity of providing an educational environment that helps to detonate the creative energies of learners.